COVID-19 autopsy in people who died in community settings: the first series. Issue 12 (30th June 2020) - Youd, Esther; Moore, Luiza
Abstract : Here, we report the pathological findings of nine complete autopsies of individuals who died in community settings in the UK, three of which were positive for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), three tested negative for SARS-CoV-2 but are likely false negatives, and three died of other respiratory infections. Autopsy revealed firm, consolidated lungs or lobar pneumonia. Histology of the lungs showed changes of diffuse alveolar damage with fibrin membrane formation, thickened alveolar walls and interstitium with lymphocytic infiltrate, and type 2 pneumocyte hyperplasia with shedding into the alveolar space. This series is the first in the world to describe autopsy findings in individuals dying suddenly in the community, not previously known to have COVID-19 infection, and the first autopsy series in the UK. During a time when testing in the UK is currently primarily offered to patients in hospital or symptomatic key workers, with limited testing available in community settings, it highlights the importance of testing for COVID-19 at autopsy. Two deaths occurred in care homes where a diagnosis of COVID-19 allowed the health protection team to provide support in that 'closed setting' to reduce the risks of onward transmission. This work highlights the need for frequent COVID-19 testing in the management of patients in community settings. Comprehensive virology and microbiology assessment is pivotal to correctly identify the cause of death, including those due to COVID-19 infection, and to derive accurate death statistics.